2020
DOI: 10.1097/fjc.0000000000000794
|View full text |Cite
|
Sign up to set email alerts
|

Artemisinin Attenuated Atherosclerosis in High-Fat Diet–Fed ApoE−/− Mice by Promoting Macrophage Autophagy Through the AMPK/mTOR/ULK1 Pathway

Abstract: Artemisinin is an endoperoxide sesquiterpene lactone from Artemisia annua L with multiple beneficial effects, including anti-inflammation, antioxidant, and vascular protection. Recent studies have found that inflammation along with autophagy deficiency in macrophages is the possible reason for foam cell accumulation in the intima, which leads to atherosclerotic plaque formation. The primary aims of this study were to explore the inhibiting effect of artemisinin on atherosclerosis in high-fat diet–fed ApoE−/− m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 31 publications
2
26
0
Order By: Relevance
“…On the other hand, a deficiency of macrophage autophagy accelerates foamy macrophage transformation (Shao et al, 2016). Treating HFD-fed ApoE-/-mice with 50, 100 mg/kg/d artemisinin for 8 weeks successfully attenuated foamy macrophage transformation and enhanced macrophage autophagy (Cao et al, 2020). Similar results were obtained in the experiments performed in vitro.…”
Section: Potential Benefits Of Treating Diabetic Cardiovascular Diseasupporting
confidence: 75%
See 2 more Smart Citations
“…On the other hand, a deficiency of macrophage autophagy accelerates foamy macrophage transformation (Shao et al, 2016). Treating HFD-fed ApoE-/-mice with 50, 100 mg/kg/d artemisinin for 8 weeks successfully attenuated foamy macrophage transformation and enhanced macrophage autophagy (Cao et al, 2020). Similar results were obtained in the experiments performed in vitro.…”
Section: Potential Benefits Of Treating Diabetic Cardiovascular Diseasupporting
confidence: 75%
“…Abundant evidence shows that after artemisinin therapy, the area of aortic root lesions shrunk, vascular smooth muscle cell hyperplasia and fibrosis were attenuated, and the progression of atherosclerosis lesion formation was diminished, indicating the potential therapeutic effects on atherosclerosis, which is one of the most common manifestations of diabetic cardiovascular disease. Thus, we deduced that artemisinins may alleviate diabetic cardiovascular disease by inhibiting the occurrence and development of atherosclerosis (Wang et al, 2013;Jiang et al, 2016;Du et al, 2019;Cao et al, 2020;Jiang et al, 2020).…”
Section: Potential Benefits Of Treating Diabetic Cardiovascular Diseamentioning
confidence: 99%
See 1 more Smart Citation
“… COX-2 inhibition. Cavin et al., 2005 18 Artemisinin Cadinanolide Artemisia annua Vascular protection ( in vivo ) Antidiabetic ( in vivo ) MCP-1, IFN-γ, IL-6 and TNF-α (↓) Inhibition of atherosclerotic plaque formation Promote the conversion of pancreatic glucagon-producing α cells to insulin-secreting β cells Cao et al., 2020 ; Li et al., 2017 19 Scoporanolide Guaianolide Artemisia scoparia Antihypertensive ( in vivo ) Inhibition of plasma ACE activity Cho et al., 2016 20 Estafiatin 21 Cumambrin A Guaianolide Chrysanthemum boreale Antihypertensive ( in vivo ) Vasorelaxant ( ex vivo ) Normalization of blood pressure Hong et al., 1999 , 2005 Reduction (↓); increment (↑); thiobarbituric acid reactive substances (TBARS); reduced glutathione (GSH); superoxide dismutase (SOD); catalase (CAT); glutathione peroxidase (GPx); insulin resistance (IR); Toll-like receptor 4 (TLR4); c-Jun N-terminal kinases (JNK); interleukin 6 (IL-6); monocyte chemoattractant protein 1 (MCP-1); Apolipoprotein C3 (APOC3); AMP-activated protein kinase (AMPK); peroxisome proliferator-activated receptors α and γ (PPARα/γ); nuclear factor kappa B (NF-κB); transforming growth factor beta (TGF-β1); fibronectin (FN); glucose-6-phosphatase (G6Pase); glucokinase (GK); cyclooxygenase 2 (COX-2); interferon-gamma (IFN-γ); tumor necrosis factor α (TNF-α); angiotensin I-converting enzyme (ACE). …”
Section: Search Strategymentioning
confidence: 99%
“…Experimental studies have also established their effectiveness as an anti-inflammatory, antioxidant, anti-tumor, and vascular protection agent ( Kim et al., 2015 ; Jiang et al., 2016 ; Efferth, 2017 ). Regarding to vascular protection, Cao et al. (2020 ) demonstrated that oral administration of artemisinin ( 18 ) effectively alleviated inflammatory response (MCP-1, IFN-γ, IL-6 and TNF-α), elevated macrophage autophagy, suppressed foamy macrophage transformation, and thereby inhibiting atherosclerotic plaque formation in high-fat diet treated ApoE −/− mice.…”
Section: Slns Isolated From Medicinal Plants and Their Potential Rolementioning
confidence: 99%